The Influence of Working Capital Turnover and Receivable Turnover on Current Ratio at PT. Kalbe Farma Tbk - Suraya, Amthy (PINISI Discretion Review, 2018)
Receivables turnover and working capital turnover are very important for a company. This study aims to determine the Working Capital Turnover and Receivable Turnover has an influence or not on the Current Ratio at PT. Kalbe Farma Tbk during the period 2009-2016. The research method is descriptive and associative using a quantitative approach. This method illustrates the company's financial condition based on real data collected from several sources obtained which are then processed and analyzed so as to obtain a systematic picture and conclusions can be drawn. The coefficient of determination is indicated by the number 0.716 which concluded that the working capital turnover and accounts receivable turnover contributed 71.6% to the current ratio, while 28.4% was influenced by other factors not examined. And the results of the F test show that Fcount> Ftable (6.303> 5.99) and significant (0.043 <0.05) which means that based on the criteria in the F test the hypothesis is accepted. Then the conclusion is working capital turnover and accounts receivable turnover has a significant effect on the current ratio.